Employee Competency Development Strategy At The Ministry Of Youth And Sports - Retna Purwaningsih; Ridwan Rajab; Firman Hadi Rivai (Jurnal Ilmu Sosial Mamangan, 2023)
This abstract provides an overview of strategies aimed at developing employee competencies within the Ministry of Youth and Sports. The satisfaction of employee entitlements in competency enhancement at the Ministry of Youth and Sports has not been met and is founded on employee competency enhancement strategies in accordance with organizational requirements. The research objectives : 1) Knowing the process of developing the competence of Kemenpora employees; and 2) Know the strategy needed to develop Kemenpora employee competencies. The research methodology used is descriptive research with a qualitative approach. The strategy for enhancing employee skills at Kemenpora is implemented by examining the requirements for training (Noe, 2010) through an analysis of the organization, analysis of tasks, and analysis of individuals, as well as various methods of developing competencies. The results of the study show that the competency development process at the Ministry of Youth and Sports has not run optimally due to the absence of: 1) Guidelines; 2) Position Competency Standards; 3) The ranking/priority is not objective; 4) Human Capital Development Plan; 5) employee competency gaps; and 6) Competency Development Information System. Leadership commitment is not optimal, but it is getting better. Most employees are interested in participating in competency development but have not had a sustainable career development impact. Competency development strategies at the Ministry of Youth and Sports, namely: 1) Leaders establish policies and Position Competency Standards; 2) Funding the budget according to the Main Performance Indicators and Strategic Plan; 3) Prepare a Human Capital Development Plan; 4) Encouraging employees to take part in Diklatpim (structural officials), functional and technical (classical/non-classical) training; 4) Bimtek with related stakeholders; 5) Socialization of all employees; and 6) Competency Development Information System Infrastructure.